Epidemiology and site specificity of stress fractures - Bennell, K. L.; Brukner, P. D. (Clinics in Sports Medicine, 1997)
Stress fractures have been reported to occur in association with a variety of sports and physical activities. Clinical impression suggests that stress fractures are more common in weightbearing activities, particularly those involving a running or jumping component. It is difficult, however, to compare the incidence of stress fractures in different sports or to identify the sport or activity with the greatest risk because of a lack of sound epidemiologic data. This article reviews the descriptive epidemiology of stress fractures, particularly methodology issues, injury rates, injury characteristics, and injury morbidity. Most of the literature in this area pertains to female runners and to male military populations. There is no information about stress fracture rates in the general community.